THE DOUBLE EMPATHY PROBLEM AS A DIALOGIC SENSE-MAKING STYLE ASYMMETRY (Romanian Journal of Analytic Philosophy, 2025)
The occurrence of social comprehension difficulties when people living with autism, henceforth: autistics,2 interact with neurotypicals motivates the re-emergence of key questions about the mind and its interaction with other minds; what are minds and how do they relate to the world and others? The disruption of smooth social interaction brings forth the question of how is a mind able to socially interact and this question motivates one to tacitly provide a definition of what a mind is. This is visible in Simon-Baron Cohen’s exposition of the theory of mind theory, henceforth: ToM, in his book Mindblindness. In this book, Baron Cohen states that autistics have at least a degree of mindblindess and that mindreading3 is the means through which the mind relates to other minds.4 His tacit descriptions of ontological properties of the mind, henceforth: ontological descriptions or assertions, are utterly different from those provided by enactivists and by those who contribute to the 20th century tradition of phenomenology, henceforth: phenomenologists.5 The tension between the ontological descriptions of ToM Theory and those provided by enactivists and phenomenologists has led to a thriving battle ground.This article’s key aim is to provide descriptions that facilitate enactivist or phenomenological analyses that engage with the double empathy problem hypothesis. To bring its aim to fruition, I follow three steps. Firstly, I define the approaches and concepts I use: phenomenology, enactivism, and the double empathy problem. Secondly, I argue in favor of using phenomenology and enactivism for explaining social difficulties in autism by presenting two, at least prima facie, disadvantages of Baron Cohen’s articulation of ToM theory; one disadvantage stems from the ethical implications of his ontological assertions and the other stems from his ontological assertions. Thirdly, I describe autistic-neurotypical social interactions in a non-pathologizing manner by performing an enactivist analysis of the double-empathy problem surrounding autistic-neurotypical social interactions.
Keywords: double empathy problem; enactivism; dialogic sense-making